Analisis Keputusan Pembelian Pada Rumah Makan Tradisional Di Sumbawa - Rizqi, Reza Muhammad; Masniadi, Rudi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine (1) the effect of price on purchasing decisions at traditional restaurants in Sumbawa (2) the effect of quality on purchasing decisions at traditional restaurants in Sumbawa (3) the effect of location on purchasing decisions at traditional restaurants in Bengawan, Raberas Resto, Sidodadi in Sumbawa. This research includes associative quantitative research. The population in this study were all consumers at traditional food restaurants in Sumbawa. The sampling method used the criteria that are consumers who are over 17 years old. The type of data is primary data obtained from the results of filling out a questionnaire with a 4-point Likert scale assessment. The analysis prerequisite test includes a linearity test, normality test, multicollinearity test, and heteroscedasticity test and the analytical technique used is multiple linear regression analysis.